تحليل الأخطاء فى التراكيب النحوية وعلاقتها بتقدم طلاب قسم اللغة العربية وآدابها فى الجامعة الإسلامية العالمية بماليزيا /‏ - ترك، ريم عادل صابر (al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2012)
This study aims to identify the syntax errors in the writing of students at the International Islamic University of Malaysia, mainly in the Department of Arabic language, the types and sources of these errors, and the difficulties faced by Malay-speaking students when they use Arabic. Finally, the extent of progress students make during the course of their study is also examined .The descriptive methodology was used in the first part of the study and the analytical approach in the proceeding chapters.The study reveals that the difficulty learners face lies in the unique system of the Arabic Language such as syntax and the accordance of gender and number. This means that their native language does not have a significant influence when they learn Arabic. The study also found that the students in the Department of Arabic language at the International Islamic University of Malaysia are making progress in their grammatical performance.